Video-assisted thoracoscopic surgery versus stereotactic radiotherapy for early stage lung cancer: what is the best treatment? - Gonzalez-Rivas, Diego (Video-Assisted Thoracic Surgery; Vol 1 (August 2016): Video-Assisted Thoracic Surgery, 2016)
Anatomic major pulmonary resection has long been considered the standard of care for Stage I with cure rates of 50–90% (1). Traditionally, the standard treatment was too agressive: open approach by means of thoracotomy, anesthetic control with a double lumen tube, epidural, central venous catheter, arterial line and urinary catheter.